2019
DOI: 10.3390/insects10080228
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Species, Strains, and Growth Media Mediate Attraction of Drosophila suzukii (Diptera: Drosophilidae)

Abstract: Specific ecological interactions between insects and microbes have potential in the development of targeted pest monitoring or control techniques for the spotted wing drosophilid, Drosophila suzukii (Matsumura), an exotic invasive pest of soft fruit. To evaluate D. suzukii attraction to yeast species from preferred types of fruit, three yeasts were isolated from blackberry fruit and two yeasts from raspberry fruit and used to bait simple plastic bottle traps. Saccharomyces cerevisiae and Hanseniaspora uvarum w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 35 publications
3
28
1
Order By: Relevance
“…A similar oviposition curve with a slow increase in egg laying was observed by Jaramillo et al (2015). Lasa et al (2019a) showed that different growth media influence the attractiveness of yeasts to SWD. A significant difference in the fecundity was observed between yeast growing media with higher oviposition on PDA compared to MEA.…”
Section: Discussionsupporting
confidence: 71%
“…A similar oviposition curve with a slow increase in egg laying was observed by Jaramillo et al (2015). Lasa et al (2019a) showed that different growth media influence the attractiveness of yeasts to SWD. A significant difference in the fecundity was observed between yeast growing media with higher oviposition on PDA compared to MEA.…”
Section: Discussionsupporting
confidence: 71%
“…It thus appears that H. uvarum is often found associated with D. suzukii; however, H. uvarum is also very common on fruits including cherries, raspberries 22 , apples, plum, pears 25 and grapes 26 and so this association may simply reflect the fact that insects visiting fruits pick up common yeast as they do. Further, while specific H. uvarum isolates are attractive to specific D. suzukii lines in laboratory studies 18 , 27 , 28 , H. uvarum is also attractive to other Drosophila species, including D. melanogaster 15 , 17 , 18 , 29 . Together this suggests that the D. suzukii: H. uvarum relationship is not specific.…”
Section: Introductionmentioning
confidence: 99%
“…The attractiveness of yeast early in the season has been previously reported [13,17]. In a recent study, yeast species, strain, and growth media were found to influence the attraction of D. suzukii flies to baited traps [20]. Yeast-based baits tend to attract many nontarget insects, including beneficials [13].…”
Section: Discussionmentioning
confidence: 99%